PERBANDINGAN CAPITAL ASSET PRICING MODEL DAN ARBITRAGE PRICING THEORY DALAM MEMPREDIKSI RETURN SAHAM LQ45 YANG TERDAFTAR DI BURSA EFEK INDONESIA (PERIODE 2018-2020) - Gea, Jerni Natalia; Silalahi, Donalson (Jurnal Manajemen dan Bisnis, 2022)
Investors in investing in the capital market need to pay attention to two things, namely: the level of risk and the expected return. In determining the expected return, the CAPM and APT methods can be used. This study is intended to identify and explain which method is more accurate in predicting returns. To achieve this purpose, a study was conducted on the shares of companies included in the LQ45 group on the Indonesia Stock Exchange with a sample of 33 company shares with a research period of 2018 - 2020. By using the t test on MAD it can be stated that: the CAPM method is more accurate in predicting returns expected when compared with the APT method